Pengembangan Bahan Ajar Buku Saku Digital Pada Mata Pelajaran PPKn Kelas XI IPS SMAN 8 Kota Jambi - Pradeva Zebua, Yan Fitra; Irwan; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2023)
This study aims to find out if there are problems experienced by class XI IPS students at SMAN 8 Jambi City for the 2021/2022 academic year when students experience teaching and learning activities. This research was conducted at SMAN 8 Jambi City on October 17 2022. The research data was obtained by distributing questionnaires to students (as the main data) and interviewing teachers in the field of Pancasila and Citizenship Education (as supporting data). After the questionnaire was returned, the data was analyzed quantitatively and qualitatively by percentage. The results showed that in the process of teaching and learning activities students did not pay attention when the teacher explained the material due to the lack of teaching materials that made students interested. The average score that did not reach the KKM was 132 or 54% of students and only 112 or 46% of students who reached the KKM. it uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), develops digital pocket book teaching materials for administering tests to determine student learning outcomes. The instruments used in this study were media expert assessment questionnaires, material experts, linguists, teacher and student responses as well as student learning outcomes. Based on the results of research conducted by giving tests in the form of questionnaires on student learning outcomes at the end of the lesson, 28 students obtained complete grades and only 2 students did not complete out of a total of 30 students so that 93% of students achieved KKM. Based on the description above, it can be concluded that the digital pocket book teaching materials that have been made can improve student learning so that this digital pocket book teaching material can be used by teachers and students of class XI IPS SMAN 8 Jambi City on PPKn material.